Psoriasis: advances in pathophysiology and management. Issue 985 (7th November 2007) - MacDonald, A; Burden, A D
Abstract : Psoriasis is an inflammatory skin disease that affects 13 of Caucasian populations and may be persistent, disfiguring and stigmatising. There is a range of severity, but even when the affected body surface area is relatively limited the impact on day-to-day activities and social interactions may be significant. An understanding of the psychological burden and an appreciation that many patients are currently dissatisfied with their management has driven the development of more effective treatment. In recent years psoriasis has been the focus of intense investigation resulting in an improved understanding of the immunopathogenesis, and the development of new, targeted biological treatments.